Structure-Conduct-Performance Analysis of China’s Sanitary Napkin Industry (Journal of Fiber Bioengineering and Informatics, 2024)
Sanitary napkins are indispensable personal care products for women. China is the largest market forfeminine hygiene products in the world. China’s sanitary napkin industry is also large and stable, withannual sales reaching billions. However, despite the promise and potential of China’s sanitary napkinindustry, there are few studies on it. In this study, anchored on industrial organisation theory and thestructure-conduct-performance (SCP) paradigm, the characteristics of China’s sanitary napkin industrywill be explored through three specific aspects: structure, conduct, and performance. Structure refersto the degree and nature of competition for products and services of an industry. Conduct is the marketpolicies sellers adopt to achieve certain objectives, such as pricing and non-pricing. Performance is theoutcomes reflecting the effects of market operation. The analysis will be conducted from the three aspectsrespectively. The results demonstrate that: (i) the market type of China’s sanitary napkin industry hasshifted from competition to oligopoly V and has highly advertising-dependent product differentiation;(ii) cost-plus pricing conduct is adopted, and advertising sponsorship and channels construction havebecome a focus in this industry; (iii) the profit level of China’s sanitary napkin industry is relatively highbut declining, and the industry scale structure needs to be improved. This study provides a theoreticalperspective on the current standing of China’s sanitary napkin industry, which can assist the industryin growing steadily.
Keywords: China’s Sanitary Napkin Industry; Market Structure; Market Conduct; Market Performance.